ADAPTATION OF HEXACO-PI-R TO THE ARMENIAN SAMPLE - Serobyan, A. K. (Modern Psychology, 2020)
Six-factor personality traits model is developing in parallel with the Big Five. The HEXACO-PI-R (HEXACO Personality Inventory - Revised) questionnaire is designed to diagnose six dispositional personality traits – Honesty/Humility, Emotionality, Extraversion, Agreeableness, Conscientiousness and Openness to Experience. The purpose of our research was the adaptation of the HEXACO PI-R questionnaire to the Armenian sample. The stages of the questionnaire adaptation to the Armenian sample included: parallel translation; expert assessment of the content of the statements and their compliance with the English original; analysis of the normal distribution of the factors and facets and, if necessary, statements correction; checking the reliability and validity of the questionnaire. Thus, the psychometric characteristics of the adapted HEXACO-PI-R questionnaire turned out to be satisfactory and do not prevent its use in the Armenian sample.
Keywords: personality traits; six factor model of personality; questionnaire adaptation; HEXACO PI-R questionnaire